Exploiting fast detectors to enter a new dimension in room‐temperature crystallography. (1st May 2014) - Owen, Robin L.; Paterson, Neil; Axford, Danny; Aishima, Jun; Schulze‐Briese, Clemens; Ren, Jingshan; Fry, Elizabeth E.; Stuart, David I.; Evans, Gwyndaf
<x xml:space="preserve">Abstract</x> A departure from a linear or an exponential intensity decay in the diffracting power of protein crystals as a function of absorbed dose is reported. The observation of a lag phase raises the possibility of collecting significantly more data from crystals held at room temperature before an intolerable intensity decay is reached. A simple model accounting for the form of the intensity decay is reintroduced and is applied for the first time to high frame‐rate room‐temperature data collection.